2020
DOI: 10.1080/10717544.2020.1803449
|View full text |Cite
|
Sign up to set email alerts
|

Thiopental sodium loaded solid lipid nano-particles attenuates obesity-induced cardiac dysfunction and cardiac hypertrophy via inactivation of inflammatory pathway

Abstract: This work evaluates solid lipid nanoparticles of thiopental sodium against obesity-induced cardiac dysfunction and hypertrophy and explores the possible mechanism of action. TS loaded SLNs were formulated by hot-homogenization and solvent diffusion method. TS-SLNs were scrutinized for entrapment efficiency, drug loading capacity, gastric stability, particle size, in vitro drug release. Mice were feed with the normal chow or high-fat diet for 08 weeks to induce obesity and primary cardiomyocytes. The therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In the present study, stearic acid and lecithin were used as a lipid matrix and surfactant, respectively and in the aqueous phase, water was used along with Tween 80. Similarly, in different studies, stearic acid was used as a lipid matrix (Fazly Bazzaz et al., 2018; Singh et al., 2014; Trucillo & Campardelli, 2019), lecithin (Andrade et al., 2019; Singh et al., 2014; Trucillo & Campardelli, 2019) as a surfactant, and Tween 80 (Andrade et al., 2019; Zhu et al., 2020) as a co‐surfactant for the synthesis of SLN, which is comparable to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, stearic acid and lecithin were used as a lipid matrix and surfactant, respectively and in the aqueous phase, water was used along with Tween 80. Similarly, in different studies, stearic acid was used as a lipid matrix (Fazly Bazzaz et al., 2018; Singh et al., 2014; Trucillo & Campardelli, 2019), lecithin (Andrade et al., 2019; Singh et al., 2014; Trucillo & Campardelli, 2019) as a surfactant, and Tween 80 (Andrade et al., 2019; Zhu et al., 2020) as a co‐surfactant for the synthesis of SLN, which is comparable to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it also possesses anti-inflammatory properties. In a study of a high-fat diet-induced cardiac hypertrophy model in obese mice, it was found that thiopental sodium lipid nanoparticles attenuated cardiac damage, hypotension, and myocardial hypertrophy induced by obesity-induced cardiac insufficiency by suppressing the inflammatory pathway and also significantly altered cardiac remodeling function, aortic function, oxidative stress, and the inflammatory response [ 135 ]. The cardioprotective effect of sodium thiopental provides evidence for future treatment of obesity and related cardiovascular complications via inflammatory pathways.…”
Section: Biomaterial-assisted Anti-obesity Therapymentioning
confidence: 99%